BLOOD INDICES DURING MENSTRUATION AND LATE FOLLICULAR PHASE OF MENSTRUAL CYCLE OF UNMARRIED YOUNG GIRLS - Omorogiuwa, Arthur; Igeleke, Tosin (Pakistan Journal of Physiology, 2014)
Background: Menstruation, which is a physiologic cyclical bleeding per vagina normally, indicates that pregnancy did not occur, while the follicular phase of the menstrual cycle is the preparatory phase for another pregnancy. This study compares the haematological values during menstruation and late follicular phases of the menstrual cycle of unmarried young adults. Method: Sixty subjects with 30 subjects each in the ovulation and luteal phases of the menstrual cycle were studied. Ethical clearance and informed consent were obtained for the study. 5mls of blood were collected using aseptic technique into a specimen bottle containing EDTA and haematological parameters were analysed using the Swelab Alfa automatic haematology analyser. Results: Red Blood Cell count value for the menstruation and follicular phases were 4.69±0.14 and 4.90±0.15 (´106/µL) respectively (p<0.05). The haematocrit for the menstruation and follicular phases were 36.41±1.03% and 38.57±0.90% respectively (p<0.05). The haemoglobin values for menstruation and follicular phases were 10.54±0.28 and 10.83±0.18 g/dL respectively (p<0.05). The platelet and white blood cell indices were essentially the same in both phases. Conclusion: The haematological change in the phases of the menstrual cycle studied is essentially that of erythropoiesis, as changes were not observed in platelets and white cell indices. Pak J Physiol 2014;10(1–2):12–4